Visualization Analysis of Foreign Negotiated Interaction Research Based on CiteSpace - Qianqian Zhang (Journal of Linguistics and Communication Studies, 2024)
This paper conducts a visual analysis of negotiation-related research in foreign English-language core journals from 2013 to 2022, totaling 83 articles, using the Web of Science core collection as the database and the bibliometric tool CiteSpace 6.1.R6 software. The aim is to illustrate the annual publication volume, main countries (regions) and institutions involved, high-impact literature, and research hotspots. The results of the visual analysis show that the publication volume of foreign negotiation research is generally increasing. The United States and Spain are the main countries conducting negotiation research. The research hotspots in foreign negotiation mainly focus on the influence of various factors (learner proficiency, task, age, interaction modes, etc.) on the nature, strategies, and patterns of negotiation, with particular attention to the semantics and forms of negotiation, interaction and second language acquisition, and feedback during the negotiation process. The findings contribute to understanding the knowledge structure and development trajectory of negotiation research in foreign contexts.